Emotional Intelligence, Integrated Supply Chain Management, Employee Commitment and Creative Behavior in Indonesian Hospitals - Yuningsih Yuningsih (International Journal of Supply Chain Management, 2020)
The purpose of this study is to examine the relationship between emotional intelligence (EI), employee commitment (EC), psychological well-being and employee creative behavior. This study investigated that how EI alter EC and employee creative behavior. Employee creative behavior is lacking among the employees of health organizations in Indonesia, that is the reason health organizations were selected in this study. Therefore, population of the study is based on health organizations of Indonesia. Data were collected from doctors by distributing questionnaire. Total 340 responses were utilized in the current study to collect the data. By using Partial Least Square (PLS), it is found that EI has crucial role to promote employee creative behaver with the help of EC and psychological well-being. EI and psychological well-being have positive effect on EC. Moreover, EC has positive effect on employee creative behavior. Furthermore, EC and psychological well-being are playing the role of mediation and moderation, respectively. Besides, our study also found that there is a significant and positive impact of integrated supply chain management practices on the creative behavior of the employees in hospital sector of Indonesia.